2012
DOI: 10.1029/2011jf002120
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple bed load measurements: Toward the identification of bed dilation and contraction in gravel‐bed rivers

Abstract: [1] This study examines bed load transport processes in a small gravel-bed river (Béard Creek, Québec) using three complementary methods: bed elevation changes between successive floods, bed activity surveys using tags inserted into the bed, and bed load transport rates from bed load traps. The analysis of 20 flood events capable of mobilizing bed material led to the identification of divergent results among the methods. In particular, bed elevation changes were not consistent with the bed activity surveys. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…This computation assumed no nontransport 374 mechanisms of volumetric change, previously termed bed deflation or contraction and 375 inflation or dilation (Merz et al, 2006;Marquis and Roy, 2012). In addition, if a raster 376 cell erodes and then fills in between surveys, no change will be detected in that cell: a 377 process known as compensating scour and fill .…”
Section: Sediment Budgeting 371mentioning
confidence: 99%
“…This computation assumed no nontransport 374 mechanisms of volumetric change, previously termed bed deflation or contraction and 375 inflation or dilation (Merz et al, 2006;Marquis and Roy, 2012). In addition, if a raster 376 cell erodes and then fills in between surveys, no change will be detected in that cell: a 377 process known as compensating scour and fill .…”
Section: Sediment Budgeting 371mentioning
confidence: 99%
“…Other bed state controls include the degree of overlap, interlocking and imbrication among grains, and bed compaction or dilation (e.g., Parker, 1990;Wilcock and Crowe, 2003;Sanguinito and Johnson, 2012;Buscombe and Conley, 2012;Mao, 2012;Kirchner et al, 1990;Marquis and Roy, 2012;Powell and Ashworth, 1995;Richards and Clifford, 1991;Ockelford and Haynes, 2013). By combining experimental data and a numerical model, Measures and Tait (2008) show that increasing grain-scale bed roughness tends to shelter downstream grains, reducing entrainment.…”
Section: Previous Work: Mechanistic Controls On τ * Cmentioning
confidence: 99%
“…A recent study describing bed dilation (changes bed elevation, increasing or decreasing respectively, in the absence of bed mobilization) and contraction found the release of fine sediment from a gravel bed is complex (Marquis and Roy, 2012). Marquis and Roy (2012) employed a variety of methods to measure bed load transport and bed mobility, including surveying bed elevation change, bed activity tags and bed load traps. The objective of their study was to understand the dynamics of the bed and its relationship to bed load transport under a variety of flood conditions.…”
Section: Mobilization Of Cohesive Sediment From Coarse Bedsmentioning
confidence: 99%
“…The study confirmed gravel bed dilatation and contraction occurred during smaller flood events and has implications for the release of cohesive sediments from a stable gravel bed. Marquis and Roy (2012) found that when a bed contracted there was a subsequent increase in fine sediment (sand) in the bed load traps, indicating the fine sediments comprising the bed matrix are mobilized from the bed as the framework particles reorganized and packed together. If cohesive sediments are entrapped within the sand matrix as previously reported (Schalchi, 1992;Rehg et al, 2005;Krishnappan and Engel, 2006), it will likely be mobilized in conjunction with the fine sediment (sand) during the process of bed contraction.…”
Section: Mobilization Of Cohesive Sediment From Coarse Bedsmentioning
confidence: 99%
See 1 more Smart Citation